Implementasi Supervisi Akademik Kepala Madrasah dalam Meningkatkan Profesionalitas Guru di Pondok Pesantren Subulussalam (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
The head of the madrasah as the leader of the madrasah has a very difficult task in order to improve the quality of the madrasah. Teachers as an important component in education, especially in terms of overcoming various problems related to improving the quality of education, are required to become professional teachers. Minister of National Education Regulation no. 12 of 2007 states that one of the competencies of madrasah heads is that they must have good supervision competencies. "This supervision includes supervising and coaching teachers who are the responsibility of the madrasa head in their coaching. Research objective (1) is to determine the implementation of academic supervision of madrasa heads at the Subulussalam Islamic boarding school. (2) to determine the professionalism of teachers at the Subulussalam Islamic boarding school. In this research, the research uses qualitative methods. This research method uses descriptive qualitative. Meanwhile, data collection uses observation, interviews and documentation. The primary data sources are the madrasa head, deputy madrasa head, and teachers. The secondary sources are through documents, interviews and photos. The results of this research are (1) the implementation of academic supervision of madrasa heads at the Subulussalam Islamic Boarding School which is carried out through several stages, starting from the planning stage, implementation, to the follow-up stage. (2) the professionalism of teachers at the Subulussalam Islamic boarding school is quite good, because seen from the indicators of teacher professionalism, namely teachers are able to master teaching materials/materials, teachers are able to manage the class, teachers are able to understand students, teachers are able to manage the class, and teachers are capable of learning methods.